Comments on ultra-high-resolution STEM - Cowley, J.M. (Ultramicroscopy, 2001)
The resolution of an image in a scanning transmission electron microscope may be improved if an image of the specimen is recorded for each point in the nanodiffraction pattern. It is shown that the method suggested by Rodenburg et al. (Ultramicroscopy 48 (1993) 304) may serve as the basis for an experimentally feasible scheme in which a resolution of better than 0.1nm is achieved for regions of 1nm diameter chosen from normal STEM images.